2020
DOI: 10.1002/bit.27332
|View full text |Cite
|
Sign up to set email alerts
|

Systems metabolic engineering of Bacillus subtilis for efficient biosynthesis of 5‐methyltetrahydrofolate

Abstract: 5‐Methyltetrahydrofolate (5‐MTHF) is the major form of folate in human plasma and is the only folate form that can penetrate the blood–brain barrier. It has been widely used for the prevention and treatment of various diseases. It is mainly produced by chemical synthesis. However, the low production rate cannot meet the increasing demand. In addition, chemical synthesis is potentially detrimental to the environment. Despite various microorganisms synthetizing 5‐MTHF, an efficient 5‐MTHF bioproduction approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…38 This study assessed the impact of the global metabolic network on 5-MTHF through transcriptome analysis results and identified relevant key genes. Therefore, we selected wild-type B. subtilis 168 (CK), 5-MTHF low-producing strain A7 obtained from previous studies (0.89 mg/L of 5-MTHF 21 ), and 5-MTHF highproducing strain A9 (1.72 ± 0.04 mg/L of 5-MTHF) for transcriptional analysis. The results of the analysis were screened according to the standard of difference significance (gene expression changed more than 2-fold and q-value (adjusted p-value) ≤ 0.05) and expression fold changes of gene up-and down-regulation (Supplementary Figure S2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…38 This study assessed the impact of the global metabolic network on 5-MTHF through transcriptome analysis results and identified relevant key genes. Therefore, we selected wild-type B. subtilis 168 (CK), 5-MTHF low-producing strain A7 obtained from previous studies (0.89 mg/L of 5-MTHF 21 ), and 5-MTHF highproducing strain A9 (1.72 ± 0.04 mg/L of 5-MTHF) for transcriptional analysis. The results of the analysis were screened according to the standard of difference significance (gene expression changed more than 2-fold and q-value (adjusted p-value) ≤ 0.05) and expression fold changes of gene up-and down-regulation (Supplementary Figure S2A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Strain A9 (B. subtilis derivate), constructed in a previous study, was used as starting host strain. 21 E. coli JM109 was used as host for gene cloning. Plasmids p7s6P1, p7s6P6, p7s6P10, p7c6P1, p7c6P6, and p7c6P10 were previously constructed based on plasmid p7s6.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of MurB, MurC, and MurD at protein level suggested that there were more PG in PC than in NC, as these proteins are involved in the synthesis of PG precursors (Real and Henriques, 2006;Vasudevan et al, 2007). The GCS catalyzed the oxidative decarboxylation of glycine and was dependent on tetrahydrofolate (THF) biosynthesis (Yang et al, 2020). It is helpful to obtain energy and 5,10methylene-tetrahydrofolate, a C1 unit that is necessary for the production of serine, thymidine, and purines (Kikuchi et al, 2008).…”
Section: Proteomics Analysismentioning
confidence: 99%